The Effectiveness of the Role of Civil Servant Investigators in Enforcement of Environmental Law - M Taufiqurrahman; Joni Emirzon; Ardiyan Saptawan (Program Pascasarjana Universitas Sriwijaya, 2022)
The occurrence of environmental pollution and damage requires repressive efforts in the form of law enforcement using instruments or criminal sanctions to force legal subjects to comply with environmental laws and regulations. Environmental civil servant investigators (PPNS) have an essential role in their authority to enforce environmental law. This research aimed to explain the state of the implementation of the role of PPNS in the work area of the Regional III Section Office - Center for Environmental and Forestry Law Enforcement and Enforcement (BPPHLHK) Sumatra Region in supporting environmental law enforcement and to find out what factors influence the role of PPNS in environmental law enforcement. The role of PPNS in enforcing environmental law in the working area of Section III Palembang - BPPHLHK Sumatra Region has been following Law Number 32 of 2009. Still, there is no standard operating procedure standard that can be used as a professional guide in implementing environmental law enforcement and measuring the effectiveness of the PPNS role. Factors that influence the role of PPNS in environmental law enforcement include legal factors, law enforcement officers, facilities and infrastructure, society and culture, and organization.